PENGEMBANGAN KAPASITAS SUMBER DAYA MANUSIA PEMERINTAH DAERAH DALAM RANGKA PENINGKATAN TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Insani, Istyadi (Jurnal Borneo Administrator, 2009)
One of good governance form in Indonesia are transparency and accountability in finance management. Policy of state and local finance management at this time are Law Number  17 of 2003, Law Number  1 of  2004 and Law Number 15 of 2004 that equiped Presidential Decree Number 42 P/2000, Presidential Decree Number 80 P/2003, Government Regulation Number 24 of 2005, Government Regulation Number  39 of 2007 and Ministry of Internal Affair Regulation Number 59 P/2007.  The new arrangement of state and local finance management is based on principles: accountability, openness, utilization, and strong external examiner institute, professional and self-supporting. Proven from BPK inspection result (2004-2007) that show obsolence of quality management and responsibility of local government financial are seen from transparency and accountability indicators. If analyzed furthermore known that one of cause is lack of  quality human resources in local finance management. Implementable effort to overcomes problems are  capacities local human resources development  in finance management pass by course and non-course and  recruited to fulfill urgent requirement. In order to obtained optimal result then development local human resources  must entangles in synergic institution that related to management of local finance. Keyword: Transparency and Accountability, Local Finance Management, and Local Human Resource Development.